Effect of Coronary Disease Characteristics on Prognostic Relevance of Residual Ischemia After Stent Implantation - Yang, Seokhun; Zhang, Jinlong; Hwang, Doyeon; Lee, Joo Myung; Nam, Chang-Wook; Shin, Eun-Seok; Doh, Joon-Hyung; Hoshino, Masahiro; Hamaya, Rikuta; Kanaji, Yoshihisa; Murai, Tadashi; Zhang, Jun-Jie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: We investigated the influence of coronary disease characteristics on prognostic implications of residual ischemia after coronary stent implantation. Methods: This study included 1,476 patients with drug-eluting stent implantation and available pre- and post-percutaneous coronary intervention (PCI) fractional flow reserve (FFR) measurements. Residual ischemia was defined as post-PCI FFR ≤ 0.80. Coronary disease characteristics with significant interaction hazard ratios (HRs) for clinical outcomes with residual ischemia were defined as interaction characteristics with residual ischemia (ICwRI). The primary outcome was target vessel failure (TVF)—a composite of cardiac death, target vessel myocardial infarction, and target vessel revascularization—at 2 years. Results: The mean pre- and post-PCI FFR were 0.68 ± 0.11 and 0.87 ± 0.07, respectively. During the median follow-up duration of 2.0 years, the cumulative incidence of TVF was 6.1%. The 203 vessels (13.8%) with residual ischemia had higher risks of TVF compared to that for post-PCI FFR >0.80 (P < 0.001). ICwRI with a significant interaction HR with residual ischemia included pre-PCI SYNTAX score >17 and pre-PCI FFR ≤ 0.62. Each ICwRI had a direct prognostic effect not mediated by residual ischemia. The association between an increased TVF risk and residual ischemia was significant in patients with 0 or 1 ICwRI [hazard ratio (HR) 3.25, 95% confidence interval (CI) 1.90–5.57, P < 0.001] but not in those with 2 ICwRI (HR 0.47, 95% CI 0.14–1.64, P = 0.24). Among patients with post-PCI FFR >0.80, those with 2 ICwRI showed similar TVF risks to those with residual ischemia (HR 1.55, 95% CI 0.79–3.02, P = 0.20). Conclusions: Coronary disease characteristics including pre-PCI SYNTAX score and pre-PCI FFR affected the prognostic implications of residual ischemia. The prognostic relevance of residual ischemia was attenuated in patients with multiple interacting characteristics.